The Role of Employee Engagement in Green HRM to Create Sustainable Humanist Performance - Aldy Friyatna Dira; Gena Prasetya Noor; Mic Finanto Ario Bangun; Muhammad Aziz Winardi N; Fahmi Kamal; Kurniawan Prambudi Utomo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to determine the role of employee involvement in Green HRM to create humanist sustainable performance as an approach that links ecological principles with human resource management in order to achieve sustainable and humane organizational performance. This research method involved surveys and data analysis using multiple linear regression analysis and distribution of questionnaires and interviews as well as literature studies, after which data processing was carried out using SPSS Analysis Version 25. from companies to identify the relationship between the level of employee involvement in sustainable initiatives. The research technique used a quantitative approach using a sample of 100 respondents and was conducted in June-August 2023, the results showed a significant positive effect on employee engagement and Green HRM variables on sustainable performance increasing productivity, employee loyalty, and company reputation as well as having a positive impact on the humanist aspect, such as job satisfaction and employee welfare. These findings underscore the need to develop a Green HRM strategy that focuses on the active participation of employees in formulating, implementing and strengthening sustainable initiatives, thereby creating a more sustainable work environment.